1990
DOI: 10.1007/bf00933553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oltipraz on the susceptibility of adultSchistosoma mansoni to killing by mouse peritoneal exudate cells

Abstract: Incubation of the adult Schistosoma mansoni with the anti-schistosomal compound oltipraz (OPZ) (40 nM) resulted in a significant decrease in schistosome-reduced glutathione (GSH), a thiol compound which may have a role in protection against oxidant-mediated damage. A significant proportion (20-47%) of worms treated with OPZ became susceptible to in vitro killing by zymosan-stimulated peritoneal exudate cells from mice infected with S. mansoni or inoculated with Bacillus Calmette Guérin (BCG). Killing of the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, the protection achieved from haem aggregation is complemented by other mechanisms such as antioxidant haem‐binding proteins like the Rhodnius haem‐binding protein from the haemolymph of a blood‐sucking insect, that is capable of interacting with haem and form complexes that do not promote free radical generation [32,33,43]. Indirect evidence of the existence of oxidative stress in the worm is that, in spite of the marked reduction in respiration – which should be accompanied by a proportional decrease in the production of free radicals – the transition from the cercariae to the red cell‐eating adult female is paralleled by a dramatic increase in the levels of antioxidants such as superoxide dismutase, glutathione reductase, glutathione peroxidase, cytochrome c peroxidase, glutathione S ‐transferase (GST) and glutathione [49–51]. Moreover, it has recently been demonstrated that a novel class of antioxidant enzyme, thioredoxin peroxidase, plays a significant role in Schistosoma –host interactions by neutralisation of hydrogen peroxide [52].…”
Section: Oxidative Stress and Antioxidant Defencesmentioning
confidence: 99%
“…Therefore, the protection achieved from haem aggregation is complemented by other mechanisms such as antioxidant haem‐binding proteins like the Rhodnius haem‐binding protein from the haemolymph of a blood‐sucking insect, that is capable of interacting with haem and form complexes that do not promote free radical generation [32,33,43]. Indirect evidence of the existence of oxidative stress in the worm is that, in spite of the marked reduction in respiration – which should be accompanied by a proportional decrease in the production of free radicals – the transition from the cercariae to the red cell‐eating adult female is paralleled by a dramatic increase in the levels of antioxidants such as superoxide dismutase, glutathione reductase, glutathione peroxidase, cytochrome c peroxidase, glutathione S ‐transferase (GST) and glutathione [49–51]. Moreover, it has recently been demonstrated that a novel class of antioxidant enzyme, thioredoxin peroxidase, plays a significant role in Schistosoma –host interactions by neutralisation of hydrogen peroxide [52].…”
Section: Oxidative Stress and Antioxidant Defencesmentioning
confidence: 99%
“…Looking forward, the identification of a parasiticidal metabolite is significant as it not only facilitates an understanding of the chemistry supporting the bioactivity but also allows the convenient in vitro assessment of anti-parasite activity and identification of the mechanism of action and/or target. The known susceptibility of the schistosome to perturbation in redox conditions, including depletion of glutathione levels (Bueding et al, 1982; Mkoji et al, 1990; Williams et al, 2013), might be a good match for this prodrug's ability to form metabolites with both oxidative (quinone methides) and reductive (a thiol and conjugated phenyls) potential, and the capacity to mop up GSH in a heterodisulfide. We are currently investigating the possible effects on redox by TP thiol, including whether GSH levels are depleted in the worm.…”
Section: Discussionmentioning
confidence: 99%